Ex vivo Quantitative Proteomic Analysis of Serotonin Transporter Interactome: Network Impact of the SERT Ala56 Coding Variant - Quinlan, Meagan A.; Robson, Matthew J.; Ye, Ran; Rose, Kristie L.; Schey, Kevin L.; Blakely, Randy D. (Frontiers in Molecular Neuroscience, 2020)
Altered serotonin (5-HT) signaling is associated with multiple brain disorders, including major depressive disorder (MDD), obsessive-compulsive disorder (OCD), and autism spectrum disorder (ASD). The presynaptic, high-affinity 5-HT transporter (SERT) tightly regulates 5-HT clearance after release from serotonergic neurons in the brain and enteric nervous systems, among other sites. Accumulating evidence suggests that SERT is dynamically regulated in distinct activity states as a result of environmental and intracellular stimuli, with regulation perturbed by disease-associated coding variants. Our lab identified a rare, hypermorphic SERT coding substitution, Gly56Ala, in subjects with ASD, finding that the Ala56 variant stabilizes a high-affinity outward-facing conformation, leading to elevated 5-HT uptake, termed SERT* state, in vitro and in vivo. Hyperactive SERT Ala56 appears to preclude further activity enhancements by p38 MAPK and can be normalized by pharmacological p38⍺ MAPK inhibition, consistent with SERT Ala56 mimicking, constitutively, a high-activity conformation entered into transiently by p38⍺ MAPK activation. As SERT has been found to interact with a number of regulatory proteins, we hypothesize that changes in SERT-interacting proteins (SIPs) support the shift of SERT into the SERT* state that can best be captured comparing SERT Ala56 protein complexes with those of wildtype SERT and by defining specific interactions through comparisons to protein complexes recovered in SERT-/- mice. Using quantitative proteomics-based approaches, we identify a number of proteins previously shown to interact with SERT, as well as a number of SIPs, that demonstrate both SERT specificity and sensitivity to the Gly56Ala substitution. Network analysis of our findings uncovers a number of ASD-associated proteins, consistent with long-standing evidence of serotonergic contributions to ASD. Further investigation of these SIPs, and the pathways they engage, may afford a greater understanding of ASD as well as other brain and peripheral disorders associated with perturbed 5-HT signaling.